Investigation into methods of reducing the blocking time of differential protection during inrush conditions. - Madzikanda, Ezekiel (My University, 2008)
ABSTRACT Power transformers are key components for electrical energy transfer in a power system. Stability and security of transformer protection are important to system operation. Many maloperation cases of transformer differential protection are caused by inrush current problems. The phenomenon of transformer inrush current has been widely discussed in literature. Therefore, this research only discussed and analyzed inrush current problems to transformer differential protection. To understand the inrush current problems on differential protection, transformer simulation models were presented using Matlab/Simulink. Differential relay simulations for internal and external faults, and relay performance during current transformer saturation were performed using PSCAD. Recommendations were made on methods of reducing the blocking time of differential protection during inrush conditions.
Keywords: Inrush current; Harmonics (second and fifth); Differential protection